Fracture Fabrication of a Multi-scale, Channel Device that Efficiently Captures and Linearizes DNA from Dilute Solutions - Kim, Byoung Choul (Lab Chip, 2015)
This paper describes a simple technique for patterning channels on elastomeric substrates, at two distinct scales of depth, through the use of controlled fracture. Control of channel depth is achieved by the careful use of different layers of PDMS, where the thickness and material properties of each layer, and the position of layers relative to one another, dictate the depth of the channels formed. The system created in this work consists of a single ‘deep’ channel, whose width can be adjusted between the micron- and nano-scale by the controlled application or removal of a uniaxial strain, and an array of ‘shallow’ nano-scale channels oriented perpendicular to the ‘deep’ channel. The utility of this system is demonstrated through the successful capture and linearization of DNA from a dilute solution, by executing a two-step ‘concentrate-then-linearize’ procedure. When the ‘deep’ channel is in its open state, and a voltage is applied across the channel network, an overlapping electric double layer forms within the ‘shallow’ channel array. This overlapping electric double layer is used to prevent passage of DNA into the ‘shallow’ channels when the DNA molecules migrate into the junctional region by electrophoresis. Release of the applied strain then allows the ‘deep’ channel to return to its closed state, reducing the cross-sectional area of this channel from the micro- to the nano-scale. The resulting hydrodynamic flow and nano-confinement effects then combine to efficiently uncoil and trap the DNA in its linearized form. By adopting this strategy, we were able to overcome the entropic barriers associated with capturing and linearizing DNA derived from a dilute solution.